DIATHESIS IN SILADANG LANGUAGE - Purwanto Siwi; Susi Ekalestari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This paper is to reveal diathesis in Siladang language. Diathesis is a grammatical category that shows the relationship between the participant or subject and the action stated by the verb in the clause. In general, the languages of the world have an active-passive diathesis strategy. This research applies the theory of diathesis proposed by Lyon and adopts descriptive qualitative method in which comparative and inductive treatments are made to the collected data through phenomenological approach. The data (Siladang language) are collected from 2223 informants (native speakers of Siladang language) who live in Sipaga-paga Village and 2006 informants who live in Aek Banir Village.  Then, the data are classified based on the language features in universal language empirically. This research shows that Sialdang language has an active-passive diathesis which is one of the important characteristics in an accusative typological language. Apart from having an active-passive diathesis, Siladang language also has a medial diathesis.